PERAN GURU BIMBINGAN KONSELING DALAM MENGOPTIMALKAN KESADARAN PESERTA DIDIK - Suriyati, Suriyati; Suriati, Suriati; Anis, Muh.; Mildayanti, Mildayanti; Riska, Riska (Universitas Islam Ahmad Dahlan, 2025)
This study aims to gain an understanding of the role of guidance and counseling teachers in optimizing student awareness at SMA 21 Bone. This study uses a qualitative approach with a descriptive method to examine the role of guidance and counseling teachers in shaping the disciplined character of students at SMA Negeri 21 Bone. Data were collected through observation, interviews, and documentation. The results of the study indicate that guidance and counseling teachers play an important role in instilling discipline awareness through self-understanding, social, academic, environmental awareness, and ethics and morals. A personal approach and continuous monitoring are applied to evaluate changes in student behavior before and after guidance and counseling. Parental involvement is also a key factor in increasing discipline awareness, through structured communication and meetings to find joint solutions. In conclusion, guidance and counseling teachers have an important role in dealing with students' personal problems and increasing discipline through a holistic and collaborative approach and helping students to become individuals who care about the environment and their surrounding communities